2019
DOI: 10.1021/acs.jchemed.8b00713
|View full text |Cite
|
Sign up to set email alerts
|

Metrics and Methods Used To Compare Student Performance Data in Chemistry Education Research Articles

Abstract: Quasi-experiments are common in studies that estimate the effect of instructional interventions on student performance outcomes. In this type of research, the nature of the experimental design, the choice in assessment, the selection of comparison groups, and the statistical methods used to analyze the comparison data dictate the validity of causal inferences. Therefore, gathering and reporting validity evidence in causal studies is of utmost importance, especially when conclusions have real policy implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
(90 reference statements)
0
16
0
Order By: Relevance
“…Irby and colleagues focused more narrowly within a hybrid curriculum to better understand if students who completed an electrical conductivity experiment in a virtual environment engaged with the chemistry triplet, 24 which models the different levels of understanding in chemistry, submicroscopic, macro- scopic, and symbolic, to a different degree than students who completed a similar hands-on experiment. 25 Their study utilized a pretest−posttest alternative treatment with a control group study design 26 where there was a control section that did not use the hybrid curriculum and two treatment sections that did. The two treatment sections were staggered so that, in any given week, one section was completing a hands-on experiment while the other section was completing a virtual experiment on a different topic.…”
Section: Differences Between Traditional and Alternative Environmentsmentioning
confidence: 99%
“…Irby and colleagues focused more narrowly within a hybrid curriculum to better understand if students who completed an electrical conductivity experiment in a virtual environment engaged with the chemistry triplet, 24 which models the different levels of understanding in chemistry, submicroscopic, macro- scopic, and symbolic, to a different degree than students who completed a similar hands-on experiment. 25 Their study utilized a pretest−posttest alternative treatment with a control group study design 26 where there was a control section that did not use the hybrid curriculum and two treatment sections that did. The two treatment sections were staggered so that, in any given week, one section was completing a hands-on experiment while the other section was completing a virtual experiment on a different topic.…”
Section: Differences Between Traditional and Alternative Environmentsmentioning
confidence: 99%
“…Additionally, the nature of a meta‐analytical approach requires combining evidence bases that arise from similar research designs. This investigation focuses on quasi‐experimental and experimental comparisons given their frequency in the research literature (Mack, Hensen, & Barbera, ). Other investigative approaches such as qualitative investigations into the quality of students' written responses or quantitative measures of growth over time, generate compelling evidence in support of instructional practices but cannot be synthesized with a corpus of studies enacting comparative designs.…”
Section: Introductionmentioning
confidence: 99%
“…To answer this guiding question, we focused on the experimental designs and data collected across the studies in our sample. In order to provide an overview of the studies, we utilized the conceptual framework outlined by Mack, Hensen, and Barbera, 113 which provides operationalized definitions of different types of quasiexperimental study designs; Table 1 provides descriptions of the design types observed in the sample. Since Mack et al 113 described only quantitative studies, we added additional categories (interview, classroom observation, open-ended survey) in order to classify qualitative studies in terms of the type of data collected.…”
Section: Researchers Examined the Impact Of Pogil Instruction?mentioning
confidence: 99%
“…In order to provide an overview of the studies, we utilized the conceptual framework outlined by Mack, Hensen, and Barbera, 113 which provides operationalized definitions of different types of quasiexperimental study designs; Table 1 provides descriptions of the design types observed in the sample. Since Mack et al 113 described only quantitative studies, we added additional categories (interview, classroom observation, open-ended survey) in order to classify qualitative studies in terms of the type of data collected. In addition, we used the category other for studies that did not fit in any of the qualitative or quantitative categories; for example, the development of an instrument to measure process skills did not fit neatly into either category, because it did not report student data.…”
Section: Researchers Examined the Impact Of Pogil Instruction?mentioning
confidence: 99%
See 1 more Smart Citation